EXERCÍCIOS FÍSICOS PARA PARKINSON (Fiep Bulletin - online, 2020)
Parkinson's disease has been described by James Parkinson and is called shaking palsy. Parkinson's disease is a brain disorder with features of a disease that destroys specific neurons responsible for the release of dopamine, an important substance in the brain. It is a progressive and disabling disease in which there is a loss of pigmented neurons in the substantia nigra with decreased dopamine. Acetylcholine has an excitatory effect, whereas dopamine is inhibitory. Both are found richly in the striated body. Parkinsonism, on the other hand, has its symptoms resulting from the imbalance between these two systems. It is a neurodegenerative disease that mainly affects the basal ganglia, specifically the dopaminergic system. Although clinically characterized by the motor symptoms of resting tremor, bradykinesia and asymmetric stiffness, Parkinson's disease today also includes non-motor symptoms caused by dysfunction of multiple neuronal populations. It is the second most common neurodegenerative disease, after Alzheimer's dementia, affecting 1-2% of the population over 60/65 years in different countries. Although no risk factors are clearly identified except for age, the etiology of the disease remains unknown. With the use of bodybuilding activity after 12 months, a significant improvement in gait of the individual in question was observed. Gait that has compromised the sinister side and generates a “circumference” to achieve foot elevation at the beginning of the gait, lost this circumference and generated significant knee extension, which contributed to the improvement of gait. Therefore, it is concluded that lower limb weight training exercises contribute to the improvement of gait in individuals with Parkinson's disease.